Airway management and mechanical ventilation in acute brain injury - Seder, David; Bösel, Julian (Critical care neurology, 2017)
Patients with acute neurologic disease often develop respiratory failure, the management of which profoundly affects brain physiology and long-term functional outcomes. This chapter reviews airway management and mechanical ventilation of patients with acute brain injury, offering practical strategies to optimize treatment of respiratory failure and minimize secondary brain injury. Specific concerns that are addressed include physiologic changes during intubation and ventilation such as the effects on intracranial pressure and brain perfusion; cervical spine management during endotracheal intubation; the role of tracheostomy; and how ventilation and oxygenation are utilized to minimize ischemia-reperfusion injury and cerebral metabolic distress.
Gesehen am 17.04.2020